An Overview of School Well-Being Scale at Students of Muhammadiyah Vocational High School: A Pilot Study - Nurul Lathifah; Annisa Hutami Adi; Tri Na’imah (Proceedings Series on Social Sciences & Humanities, 2021)
The researcher conducted a psychometric analysis to know the school well-being scale’s validity and reliability and understand the dimensions that could form the school well-being variable. School well-being is a complex concept because it involves various essential elements in the teaching and learning process. School well-being is useful to help create a conducive learning environment and achieve learning goals in schools. The school well-being variable was measured using four dimensions from Konu & Rimpelä, namely having, loving, being, and health status. Forty students of SMK Muhammadiyah X in Ajibarang District, Banyumas, Indonesia, were involved. Analysis of research data to measure validity uses the corrected item-total correlation formula, while to measure reliability using Cronbach’s alpha which is analyzed using SPSS version 25. The analysis results prove that from the four dimensions of school well-being, there are 26 valid items and have a reliability coefficient of 0.903. Thus, the school well-being scale can be used for research.